In vivo hepatoprotective activity of Muntingia calabura leaves extract: a metabolomics analysis / Mohd Salleh Rofiee - Rofiee, Mohd Salleh (Institute of Graduate Studies, UiTM, 2017)
Muntingia calabura (Muntingiaceae) is known as ‘kerukup siam’ or ‘pokok buah ceri’ locally. It has been used in Southeast Asia and tropical America as antipyretic, antiseptic, analgesic, antispasmodic and liver tonic. This study aims to determine the safety and the metabolic pathways involved in the hepatoprotective mechanism of M. calabura. Phytochemical analysis of the extract was carried out. The standardization of the extracts was done using LCMS Q-TOF. The standardized extract was subjected to acute and repeated doses of 28-day oral toxicity study. Three different in-vivo hepatotoxic models which are CCl4-induced, PCM-induced and alcohol-induced were eveloped and a dose dependent hepatoprotective effect of M. calabura (100 mg/kg, 200 mg/kg and 400 mg/kg) was conducted. Body weight, food and water consumption were measured every day and rats were sacrificed to collect the serum samples at the end of the 10-days treatment for CCl4 and PCM induced hepatotoxic rats while samples were collected at the end of 22-days for alcohol-induced hepatotoxic rats. Histopathological study of the liver slice was carried out to confirm the hepatoprotective activity of the extract…